(untitled) (Journal of the College of Basic Education, 2022)
The aim of the research is to propose multiple mechanisms that contain approved criteria for evaluating university teaching performance by the direct management (department head), by teaching colleagues in the profession, and by the students he teaches.And after reviewing the literature and previous studies and benefiting from them in building the required tools and achieving the research objectives, and after the validity and reliability processes that were conducted on the tools, they were adopted and applied in the evaluation process with its three directions:Management calendar, colleagues calendar, and students calendar. The results were very useful in the process of diagnosis, indicating strengths and weaknesses, and providing meaningful feedback.The study concluded with a number of conclusions, recommendations and suggestions, and concluded with a list of considered sources that were referred to.